Back-iron extension thermal benefits for electrical machines with concentrated windings - Zhang, Fengyu; Gerada, David; Xu, Zeyuan; Zhang, Xiaochen; Tighe, Chris; Zhang, He; Gerada, Chris (2020)
This paper proposes a novel, low-cost, effective way to improve the thermal performance of electrical machines by extending a part of the back-iron into the slot. This modification helps in reducing the thermal resistance path from the center of the slot to the coolant, however its thermal benefits must be clearly evaluated in conjunction with the electromagnetic aspects, due to the higher iron losses and flux-leakage, and furthermore such an extension occupies space which would otherwise be allocated to the copper itself. Taking a case study involving an existing 75kW electric vehicle (EV) traction motor, the tradeoffs involving the losses, fluxleakage, output torque, torque-quality and the peak winding temperature with back-iron extension (BIE) and without are compared. Finally, experimental segments of the aforesaid motor are tested, verifying a significant 26.7% peak winding temperature reduction for the same output power with the proposed modification.